Clinical outcomes and anti-inflammatory mechanisms predict maximum heart rate improvement after physical activity training in individuals with psychiatric disorders and comorbid obesity - Pau Soldevila-Matías; Joan Vicent Sánchez-Ortí; Patricia Correa-Ghisays; Vicent Balanzá-Martínez; Gabriel Selva-Vera; Roberto Sanchis-Sanchis; Néstor Iglesias-García; Manuel Monfort-Pañego; Pilar Tomás-Martínez; Víctor M. Victor; Benedicto Crespo-Facorro; Constanza San Martín Valenzuela; et al. (PLoS ONE, 2025)
Introduction This study aimed to evaluate the predictive validity and discriminatory ability of clinical outcomes, inflammatory activity, oxidative and vascular damage, and metabolic mechanisms for detecting significant improve maximum heart rate after physical activity training in individuals with psychiatric disorders and obesity comorbid using a longitudinal design and transdiagnostic perspective. Methods Patients with major depressive disorder, bipolar disorder and, schizophrenia and with comorbid obesity (n = 29) were assigned to a 12-week structured physical exercise program. Peripheral blood biomarkers of inflammation, oxidative stress, vascular mechanisms, and metabolic activity, as well as neurocognitive and functional performance were assessed twice, before and after intervention. Maximum heart rate was considered a marker of effectiveness of physical activity. Mixed one-way analysis of variance and linear regression analyses were performed. Results Individuals with psychiatric disorders and comorbid obesity exhibited an improvement in cognition, mood symptoms and body mass index, increase anti-inflammatory activity together with enhancement of the oxidative and cardiovascular mechanisms after physical activity training (p<0.05 to 0.0001; d = 0.47 to 1.63). A better clinical outcomes along with regulation of inflammatory, oxidative, and cardiovascular mechanisms were critical for predicting significant maximum heart rate variation over time (χ2 = 32.2 to 39.0, p < 0.0001). Conclusions The regulation of the anti-inflammatory mechanisms may be essential for maintained of healthy physical activity across psychiatric disorders and obesity. Likewise, inflammatory activity, oxidative stress, vascular and cardio-metabolic mechanisms may be a useful to identify individuals at greater risk of multi-comorbidity.